Mediastinal cystic lymphangioma - Saleiro,Sandra (2006)
Mediastinal lymphangioma is a rare vascular neoplasm, accounting for 0.7 to 4.5% of all the mediastinum tumors. It is a benign tumor, generally occurring as a mediastinal mass of slow growth. Most patients are asymptomatic, being incidentally diagnosed after a routine chest radiograph. The best treatment consists of complete surgical resection. Prognosis depends on the degree of resecability degree, and recurrence is not expected if the lesion is totally removed.